Central Mechanism Controlling Pubertal Onset in Mammals: A Triggering Role of Kisspeptin - Uenoyama, Yoshihisa; Inoue, Naoko; Nakamura, Sho; Tsukamura, Hiroko (Frontiers in Endocrinology, 2019)
Pubertal onset is thought to be timed by an increase in pulsatile gonadotropin-releasing hormone (GnRH)/gonadotropin secretion in mammals. The underlying mechanism of pubertal onset in mammals is still an open question. Evidence accumulated in the last 15 years suggests that kisspeptin/neurokinin B/dynorphin A (KNDy) neurons in the hypothalamic arcuate nucleus play a key role in pubertal onset by triggering pulsatile GnRH/gonadotropin secretin in mammals. Specifically, KNDy neurons are now considered a part of GnRH pulse generator, in which neurokinin B facilitates and dynorphin A inhibits, the synchronized discharge of KNDy neurons in autocrine and/or paracrine manners. Kisspeptin serves as a potent secretagogue of GnRH secretion and thus its release is fundamental to pubertal increase in GnRH/gonadotropin secretion in mammals. Proposed mechanisms inhibiting Kiss1 (kisspeptin gene) expression during childhood to juvenile varies from species to species: we envisage that negative feedback action of estrogen plays a key role in the inhibition of Kiss1 expression in KNDy neurons in rodents and sheep, whereas estrogen-independent inhibition of kisspeptin secretion by γ-amino butyric acid or neuropeptide Y are suggested to be responsible for the pre-pubertal suppression of GnRH/gonadotropin secretion in primates. Taken together, the timing of pubertal onset is postulated to be controlled by upstream regulators for kisspeptin biosynthesis and secretion in mammals.